2016
DOI: 10.1017/s1751731115002098
|View full text |Cite
|
Sign up to set email alerts
|

Why are most EU pigs tail docked? Economic and ethical analysis of four pig housing and management scenarios in the light of EU legislation and animal welfare outcomes

Abstract: To limit tail biting incidence, most pig producers in Europe tail dock their piglets. This is despite EU Council Directive 2008/120/EC banning routine tail docking and allowing it only as a last resort. The paper aims to understand what it takes to fulfil the intentions of the Directive by examining economic results of four management and housing scenarios, and by discussing their consequences for animal welfare in the light of legal and ethical considerations. The four scenarios compared are: ‘Standard Docked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
95
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(98 citation statements)
references
References 37 publications
1
95
1
1
Order By: Relevance
“…This might also be an explanatory factor for why Finland can manage so well with the non-docking policy: Finnish farms are, on average smaller than in many other EU countries. On large farms, often with a reduced caretaker/pig ratio, it becomes more difficult to spot tail biting early enough, and have time to intervene appropriately [10]. However, we did not find a correlation between farm size and occurrence of tail biting in this study.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…This might also be an explanatory factor for why Finland can manage so well with the non-docking policy: Finnish farms are, on average smaller than in many other EU countries. On large farms, often with a reduced caretaker/pig ratio, it becomes more difficult to spot tail biting early enough, and have time to intervene appropriately [10]. However, we did not find a correlation between farm size and occurrence of tail biting in this study.…”
Section: Discussioncontrasting
confidence: 65%
“…Based on available studies, Valros & Heinonen [8] suggested that tail docking reduces the prevalence of severe lesions by about 50 %. Tail docking in itself, in addition to causing acute, and possibly chronic pain [9], reduces the risk of tail biting when keeping pigs in rearing systems with a higher level of risk factors, and thus might increase the risk of keeping pigs in a way that is not optimal for their welfare [8, 10]. Another important reason for favouring long-tailed pigs is that in non-docked pigs, the status of the tails can be used as a measure of the overall welfare status on the farm [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, victims of tail biting suffer from acute pain, have an increased risk of infections and a reduced weight gain. As a consequence, tail biting is not compatible with welfare and it is in the interest of pig producers to avoid economical losses due to tail biting [1, 8]. Nevertheless, the prevention of tail biting should focus on identifying and eliminating predisposing, possibly interacting risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Stress can be caused by overcrowding, frequent mixing of different litters, and too high a temperature. Tail biting, a common consequence of stress has been estimated to cost around 18 Euros per affected pig which includes medication, veterinary care and carcass condemnation (D'Eath et al, 2016).…”
Section: Introductionmentioning
confidence: 99%